Early speech and language indicators for later learning problems: recognizing a language organization disorder. - Lockwood SL (Infants & Young Children: An Interdisciplinary Journal of Early Childhood Intervention, 1994)
Children with early speech-language delays are at high risk for later developing learning problems in school. This article addresses the continuity and offers an explanation based on the demands for language organization. A descriptive term, language organization disorder, is recommended. Chronology of the difficulties and methods for early detection are provided.